Balancing privacy and openness, using a lens of contextual integrity - Cronin, Catherine (Proceedings of the International Conference on Networked Learning, 2018)
This paper describes a qualitative, empirical research study which explored the use of open educational practices (OEP) by academic staff in higher education, focusing particularly on the findings in relation to balancing privacy and openness. The study explored meaning-making and decision-making by university educators regarding whether, why, and how they used OEP. Open educational practices have been defined as “practices which support the (re)use and production of OER through institutional policies, promote innovative pedagogical models, and respect and empower learners as co-producers on their lifelong learning paths” (Ehlers, 2011, p. 4). The purpose of this study was to understand how university educators conceive of, make sense of, and make use of OEP, and to try to learn more about, and from, the practices and values of educators from across a broad continuum of ‘closed’ to open practices. The study was conducted at one Irish university using constructivist grounded theory methodology; semi-structured interviews were carried out with educators across multiple disciplines. Balancing privacy and openness emerged as a key concern of academic staff in relation to their digital and networked practices. This balancing act was described by participants, overwhelmingly, as an individual decision and an ongoing challenge: “you’re negotiating all the time.” A model was developed to illustrate how individuals seek to balance privacy and openness at four levels: macro (global level), meso (community/network level), micro (individual level), and nano (interaction level). The main finding of the study was that openness is always complex, personal, contextual, and continually negotiated. These empirical results reinforce the utility of Nissenbaum’s (2004, 2010) framework of contextual integrity in constructing a full understanding of meaning-making and decision-making with regard to open practices, and thus can contribute to effective support of academic staff in relation to open education and networked learning.